Introduction of Indonesian Heroes to Foster Nationalism Among Indonesian Community Centre Students in Pahang Malaysia - Amelia Annisa Nur Rohmah; Aisyah Aulia Eka Apriliana; Arum Dwi Asriani; Farid Aji Prakosa; Weni Hastuti (International Conference on Education for All, 2023)
This article aims to describe the implementation of nationalism among ICC Pahang students through the introduction of Indonesian national heroes. The introduction of Indonesian national heroes is very important, especially for ICC Pahang students who have never set foot in their own homeland. Therefore, this can foster a sense of nationalism and ignite a love for their homeland. The method of implementation in this activity involves providing national-themed and hero-themed materials in all classes, storytelling, and showing videos about heroism and independence during break and sharing sessions. Additionally, to boost the spirit of August 17th, a competition was held. The results of this activity include an increased love for Indonesia, as they can now feel the hardship of the struggle for Indonesia's independence. They feel the need to study diligently, especially to get to know Indonesia better, so they have a strong curiosity about Indonesian national heroes and significant events that occurred before Indonesia gained independence.